Is There a Role for Cerebral Ultrasonography in Near-Term/Term Neonates Following Assisted Vaginal Delivery? A Prospective, Single-Center Study - Poryo, Martin; Zimmer, Anika; Hamza, Amr; Wagenpfeil, Stefan; Zemlin, Michael; Geipel, Martina; Löffler, Günther; Meyer, Sascha; Tutdibi, Erol (Ultraschall in der Medizin - European Journal of Ultrasound, 2020)
Aim To evaluate the role of cerebral ultrasonography studies (CUSS) in detecting intracerebral and cranial pathologies (hemorrhages, ischemia, skull fractures) in near-term and term neonates following assisted vaginal delivery.Patients and Methods Prospective single-center study (11/2017–11/2018) at the University Children’s Hospital of Saarland, Homburg, Germany including newborns with a gestational age ≥ 36 weeks born by assisted vaginal delivery. In all newborns, a standardized CUSS was performed within the first three days of life prior to discharge.Results 200 neonates (43.0 % female, 57.0 % male; gestational age 39.6 ± 1.3 weeks) were included in this study (birth weight 3345.6 ± 450.6 g, body length 51.7 ± 2.5 cm, head circumference 35.0 ± 1.5 cm). 67 (33.5 %) neonates had minor external injuries of the scalp. 5 children showed clinical neurologic abnormalities: 4 (2.0 %) seizures and 1 facial palsy (0.5 %). In 34 (17.0 %) patients, minor incidental intracranial abnormalities unrelated to mode of delivery were detected on CUSS. No intracerebral, cranial pathologies or skull fractures were seen on routine CUSS.Conclusion Routine CUSS in newborns after assisted vaginal delivery did not yield clinically relevant results in our cohort. Clinical observation and selective CUSS in symptomatic newborns might be more efficient than routine CUSS.
Keywords: assisted vaginal delivery; vacuum extraction; cerebral ultrasonography study; hemorrhage; ischemia; skull fracture